Penggunaan Pendekatan Saintifik Model Inquiry Learning Metode Diskusi Kelompok untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik Mata Pelajaran Fiqih Pokok Bahasan Zakat di Kelas VIII.4. Semester Ganjil Tahun Pelajaran 2018 / 2019 MTsN 2 Kota Pa - Mesra Definta (Departement of Mathematics Education, 2022)
This study aims to see and analyze the increase in motivation and learning outcomes of Fiqh Discussion of Zakat in class VIII.4 Odd Semester T.P 2018/2019 MTsN 2 Payakumbuh, West Sumatra. This research was conducted using the Classroom Action Research method which consisted of two cycles, where each cycle consisted of; planning, action, reflection, and evaluation. It was carried out from August to December 2018. The data was processed in each cycle and then analyzed using percentages. The results obtained from this study are scientific methods can improve student learning outcomes to enter higher schools. This is evident from the results obtained in Cycle I increased for learning outcomes 75% from before cycle I. From Cycle I to Cycle II increased 94%. Students' learning motivation increased from 43% to 84%. The conclusion obtained from this study is that the use of a scientific approach to the Inquiry learning model can improve student learning outcomes.